2004
DOI: 10.1097/00005110-200411000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Themes Surrounding Novice Nurse Near-Miss and Adverse-Event Situations

Abstract: Findings suggest that support for novice nurses in acute care environments requires attention to the following: consistent availability of expertise in light of workload unpredictability, the social climate regarding expectations of novice performers, realistic expectations of novice decision-making ability during complex situations even up to a year after graduation, and strategies to recognize and intervene when novices are at risk for error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 6 publications
4
113
0
1
Order By: Relevance
“…The participants emphasised the importance of support from experienced nurses and their willingness to give inexperienced nurses enough time to do their job thoroughly and safely. This concurs with an earlier study (Ebright et al, 2004) that demonstrates the importance of a supportive social climate for inexperienced nurses. Other published studies confirm this conclusion (Moszczynski and Haney, 2002;Sveinsdottir et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The participants emphasised the importance of support from experienced nurses and their willingness to give inexperienced nurses enough time to do their job thoroughly and safely. This concurs with an earlier study (Ebright et al, 2004) that demonstrates the importance of a supportive social climate for inexperienced nurses. Other published studies confirm this conclusion (Moszczynski and Haney, 2002;Sveinsdottir et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Competence in process and risk management is also necessary [1] and situation-sensitivity required to prevent near misses and adverse events [1, 15,16]. Risks are often related to medicines [17][18][19][20] or to rapid changes in the patient's status [21].…”
Section: Clinical Competence and Skill Definedmentioning
confidence: 99%
“…Critical thinking skills have also been called into question (Boychuk Duchscher, 2003;del Bueno, 1994). The approach of new nurses to medication administration (Manias, Aitken & Dunning, 2004a;Manias, Aitken & Dunning, 2004b) and involvement in medication errors or near misses (Ebright, Urden, Patterson & Chalko, 2004;Smith & Crawford, 2003) has also been explored to determine their competency in dealing with the medication demands of the job. These concerns may be warranted as a recent study also found that for newly graduated nurses, competent performance was not guaranteed but rather something to celebrate (Jackson, 2005).…”
Section: Demands In the Workplacementioning
confidence: 99%